Eigen Value of Fuzzy Matrices - Suroto, Suroto; Wardayanti, Ari (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2017)
In this paper we discuss about eigen value of fuzzy matrices by adopted the substract operation of fuzzy matrices in Sidky and Emam (1992). By applying this substraction, itâs yields that some properties eigen value of fuzzy matrices in Joe Anand and Edal Anand is not satisfied.Â©2016 JNSMR UIN Walisongo. All rights reserved.